if x plus one by x square is equal to 3 then x cube + 1 y cube is equal to
Answers
Answered by
1
x+1/x = 3
cube on both sides,
(x+1/x)^3 = 3^3
by formula (a+b)^3 = a^3 +b^3+3ab(a+b)
here,
x^3 +1/x^3 + 3(x*1/x)(x+1/x) = 3^3
x^3 +1/x^3 +3(3) = 27
x^3 +1/x^3 = 27-9
x^3 +1/x^3 = 18
i hope this will help you
-by ABHAY
cube on both sides,
(x+1/x)^3 = 3^3
by formula (a+b)^3 = a^3 +b^3+3ab(a+b)
here,
x^3 +1/x^3 + 3(x*1/x)(x+1/x) = 3^3
x^3 +1/x^3 +3(3) = 27
x^3 +1/x^3 = 27-9
x^3 +1/x^3 = 18
i hope this will help you
-by ABHAY
SAPNAYADAV:
not x+1÷xbutx+1÷x whole square
Answered by
3
Hlo friend.. Cutiepie Here..
Here is ur answer :
![x + \frac{1}{x} = 3 \: \: \: \: \: \: ......(1) x + \frac{1}{x} = 3 \: \: \: \: \: \: ......(1)](https://tex.z-dn.net/?f=x+%2B++%5Cfrac%7B1%7D%7Bx%7D++%3D+3+%5C%3A++%5C%3A++%5C%3A++%5C%3A++%5C%3A++%5C%3A+......%281%29)
To find
![{x}^{3} + \frac{1}{ {x}^{3} } {x}^{3} + \frac{1}{ {x}^{3} }](https://tex.z-dn.net/?f=+%7Bx%7D%5E%7B3%7D+++%2B++%5Cfrac%7B1%7D%7B+%7Bx%7D%5E%7B3%7D+%7D+)
Let a = x
Let b = 1/x
Using identity,
( a + b)³ = a³ + b³ + 3ab( a + b)
Cube on both sides in eqⁿ (1)
![{(x + \frac{1}{x} )}^{3} = {(3)}^{3} {(x + \frac{1}{x} )}^{3} = {(3)}^{3}](https://tex.z-dn.net/?f=%7B%28x++%2B++%5Cfrac%7B1%7D%7Bx%7D+%29%7D%5E%7B3%7D++%3D++%7B%283%29%7D%5E%7B3%7D+)
![{x}^{3} + \frac{1}{ {x}^{3} } + 3 \times x \times \frac{1}{x} (x + \frac{1}{x}) = 27 {x}^{3} + \frac{1}{ {x}^{3} } + 3 \times x \times \frac{1}{x} (x + \frac{1}{x}) = 27](https://tex.z-dn.net/?f=+%7Bx%7D%5E%7B3%7D++%2B++%5Cfrac%7B1%7D%7B+%7Bx%7D%5E%7B3%7D+%7D+++%2B+3+%5Ctimes+x+%5Ctimes++%5Cfrac%7B1%7D%7Bx%7D+%28x+%2B++%5Cfrac%7B1%7D%7Bx%7D%29+%3D+27)
![{x}^{3} + \frac{1}{ {x}^{3} } + 3(3) = 27 {x}^{3} + \frac{1}{ {x}^{3} } + 3(3) = 27](https://tex.z-dn.net/?f=+%7Bx%7D%5E%7B3%7D++%2B++%5Cfrac%7B1%7D%7B+%7Bx%7D%5E%7B3%7D+%7D++%2B+3%283%29+%3D+27)
![{x}^{3} + \frac{1}{ {x}^{3} } + 9 = 27 {x}^{3} + \frac{1}{ {x}^{3} } + 9 = 27](https://tex.z-dn.net/?f=+%7Bx%7D%5E%7B3%7D++%2B++%5Cfrac%7B1%7D%7B+%7Bx%7D%5E%7B3%7D+%7D++%2B+9+%3D+27)
![{x}^{3} + \frac{1}{ {x}^{3} } = 27 - 9 {x}^{3} + \frac{1}{ {x}^{3} } = 27 - 9](https://tex.z-dn.net/?f=+%7Bx%7D%5E%7B3%7D++%2B++%5Cfrac%7B1%7D%7B+%7Bx%7D%5E%7B3%7D+%7D++%3D+27+-+9)
![{x}^{3} + \frac{1}{ {x}^{3} } = 18 {x}^{3} + \frac{1}{ {x}^{3} } = 18](https://tex.z-dn.net/?f=+%7Bx%7D%5E%7B3%7D++%2B++%5Cfrac%7B1%7D%7B+%7Bx%7D%5E%7B3%7D+%7D++%3D+18)
_______
HOPE IT HELPS..
Here is ur answer :
To find
Let a = x
Let b = 1/x
Using identity,
( a + b)³ = a³ + b³ + 3ab( a + b)
Cube on both sides in eqⁿ (1)
_______
HOPE IT HELPS..
Similar questions